Philippine history - De Guzman, Rowena R.; Borras;Diego;Olegario;Paras (Araneta Avenue : HisGoPhil Publishing House Inc., 2013)
History as he further mentioned should be viewed from a perspective that aims to point out the dignity and nobility of a people through their struggles and triumphs, through their recorded works and the thoughts of it advocates.
1. The saga Begins 2. The Filipino before the Conquest 3. Navigation and colonization 4. The Philippines under Spanish rule 5. Filipino Reaction to Foreign threats and Internal Aggression 6. The growth of Philippine Nationalism 7. Katipunan and the 1986 Philippine revolution 8. American Infiltration 9. Japanese occupation 10. The Presidents of the Philippine Republic
Includes bibliographical references.